Field notes contributed by Tanya Bray, fall 1991 - Bray, Tanyaet al (1991)
List of birds and locations contributed by Tanya Bray with observer Jerry Toll. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed